2020
DOI: 10.1111/ijlh.13389
|View full text |Cite
|
Sign up to set email alerts
|

Assessing maternal clotting function with novel global coagulation assays: A prospective pilot study

Abstract: Introduction Women are at higher risk of venous thromboembolism (VTE) during pregnancy and the puerperium. Global coagulation assays (GCAs), including thromboelastography (TEG), thrombin generation using the calibrated automated thrombogram (CAT) and fibrin generation using the overall haemostatic potential assay (OHP), provide a more comprehensive assessment of the coagulation process than conventional coagulation assays. We aimed to evaluate the ability of these GCAs to analyse the coagulability among pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
3
7
0
Order By: Relevance
“…In studies which have included postpartum measurements, it has been determined that hypercoagulability persists until at least 24 h postpartum. 50,55 Our recent study also demonstrated marked hypercoagulability in term pregnant women, 56 in particular increased alpha angle (rate of clot formation) (65.8 vs 54.1 , p < 0.001) and maximum amplitude (clot strength) (71.5 vs 60.6 mm, p < 0.001), consistent with published data. 14,[49][50][51][52][53] ROTEM has also demonstrated the hypercoagulability of pregnancy at term in several studies.…”
Section: Viscoelastic Testing -Thromboelastography and Rotational Thr...supporting
confidence: 90%
See 3 more Smart Citations
“…In studies which have included postpartum measurements, it has been determined that hypercoagulability persists until at least 24 h postpartum. 50,55 Our recent study also demonstrated marked hypercoagulability in term pregnant women, 56 in particular increased alpha angle (rate of clot formation) (65.8 vs 54.1 , p < 0.001) and maximum amplitude (clot strength) (71.5 vs 60.6 mm, p < 0.001), consistent with published data. 14,[49][50][51][52][53] ROTEM has also demonstrated the hypercoagulability of pregnancy at term in several studies.…”
Section: Viscoelastic Testing -Thromboelastography and Rotational Thr...supporting
confidence: 90%
“…66 Multiple studies with CAT demonstrate hypercoagulability in pregnancy, including a significant increase in peak thrombin generation and ETP early in pregnancy, [67][68][69][70][71][72] consistent with our recent publication. 56 We reported that term pregnant women demonstrated markedly increased ETP (1895.2 vs 1399.4 nM/min, p < 0.001), thrombin peak (320.9 vs 240.0 nM) and velocity index (110.7 vs 83.4 nM/min, p < 0.001). Joly et al reported that thrombin generation appears to increase early on in pregnancy and remained stable during pregnancy 67 although this differed to the findings by McLean et al who reported the increase of thrombin generation with pregnancy progression.…”
Section: Thrombin Generation With Calibrated Automated Thrombogrammentioning
confidence: 80%
See 2 more Smart Citations
“…Altered haemostasis is common in obstetric patients as pregnancy is associated with increases in coagulation factors and changes in pro-and anti-fibrinolytic factors [1][2][3]. Haemostatic assessment is vital for identifying and correcting major haemostatic abnormalities that can contribute to events such as postpartum haemorrhage (PPH) [4]. The timely identification of coagulopathy is paramount as obstetric haemorrhage is the leading cause of maternal mortality, accounting for 27% of the 295,000 maternal deaths reported worldwide [5].…”
Section: Introductionmentioning
confidence: 99%